Luminosidade e volume do recipiente no desenvolvimento de mudas de figueira branca (Ficus gomelleira Kunth.) e faveira-benguê (Parkia multijuga Benth.) em condições de viveiro - Maekawa, Luiz (2018)
Ficus gomelleira and Parkia multijuga are forest species which occur naturally in the northwest of Mato Grosso and are logged from the native forests for obtaining wood. Such harvesting could take place within commercial cultivation; however, it still necessary to develop researches with the purpose of increasing knowledge about the whole productive process, beginning with the production of quality seedlings. The pace of forest and riparian deforestation and timber harvesting has been quicker than the recovery of native forest. In this context, the objective of the present study was to evaluate the development of Ficus gomelleira and Parkia multijuga seedlings under different light conditions and container volumes produced in nursery. In this research, the experimental design was distributed in blocks, divided in parcels of 4 x 4 with 4 replications of 24 plants per plot, totaling 1,536 seedlings of each species. Tested light conditions were: 0 (full sunlight), 30, 50 and 70% shading. In order to evaluate the growth of Ficus gomelleira, containers with commercial substrate in the volumes of 50, 110, 290 and 400 cm³ were used and as for Parkia multijuga, containers of 110, 180, 290 and 400 cm³ were utilized. From the total number of seedlings produced, 8 central seedlings of each plot were selected, totaling 512 seedlings per species, from which the morphological parameters and their correlations were evaluated after 180 days: collar stem diameter, seedling height, number of leaves; dried mass of roots, dried aboveground phytomass, total dried mass; correlation of height and collar stem diameter; correlation of height and dried aboveground phytomass; correlation of dried aboveground phytomass and dried root mass; correlation of dried root mass and dried aboveground phytomass; Dickson Quality Index (DQI). The Ficus gomelleira seedlings presented higher growth and better quality when kept in the nursery for a period of up to 180 days in full sunlight, in tubes of 290 cm³ or containers of 400 cm³; while in the case of Parkia multijuga, the best condition was full sunlight in containers of 400 cm³. The shading of 70% for 180 days was not adequate for the production of quality seedlings in nursery of the species studied.